The Impact of Personality Traits on Job Performance - Lampe, Nuša; Lascau, Florin Daniel; Nančovska Šerbec, Irena; Meško, Maja (Izzivi managementa talentov, 2025)
The study examines the impact of personality traits on the work performance of judo referees who officiated on the World Judo Tour between 2018 and 2022. A total of 63 referees participated by completing the Big Five Inventory (BFI) and the Conditions for Work Effectiveness Questionnaire (CWEQ-II). Due to the small sample size, non-parametric methods were employed, and the data were analysed using descriptive statistics, correlation analysis, and structural equation modelling. The results show that agreeableness and conscientiousness have the strongest positive effects on job performance. Education provided by the IJF Academy significantly contributes to enhancing support and creating opportunities for referees. Older referees demonstrate greater emotional stability and responsibility, while younger referees tend to display higher levels of openness and extraversion. The research confirms that the relationship between personality traits and work performance is a key factor in referee development. The proposed model provides guidance for future training and education programs by recommending the adaptation of educational approaches to individual personality traits. Moreover, the model can be applied to other martial arts and broader sports contexts.